Paciente de 32 años de edad con absceso cerebral - Palma Jimenez, Jeniffer Josselyn (2018)
Brain abscess is a purulent infection of the brain parenchyma, it is when immune cells, pus and other materials accumulate in the brain, usually this abscess is caused by bacteria or fungi that infect part of the brain with swelling and irritation, reach the brain through of blood or directly at the time of brain surgery, the signs and symptoms that occur in this condition are altered level of consciousness such as confusion, fever or chills, headache, seizures, loss of muscle function on one side of the body , nausea, vomiting, and changes is vision, exams to detect an abscess are computer tomography of the head, magnetic resonance of the head, blood cultures and laboratory tests. This case was carried out with the aim of deepening knowledge about this pathology and by collecting data from the patient, analyzing which patterns are altered and being able to apply the nursing care processes, executing the necessary care and improving their health status. We present the case of a female patient of 32 years of age, a housewife who was assisted at the Martin Icaza General Hospital in the city of Babahoyo, through the examinations performed as biometry and computerized axial tomography of the skull. of brain abscess, the patient arrives at the unit presenting headache, asthenia and left hemiparesis, with a surgical wound because she was operated on a paracentral cyst in a clinic, the wound became infected and the abscess developed. The methods used were nursing care through the (PAE) process of nursing care, and the administration of antibiotics, anticonvulsants, anti ulcers and anti-inflammatories through which favorable results were obtained.